A Picture’s Worth a Thousand Words: Conversational versus Eyewitness Testimony in Criminal Convictions - Duke, Steven B. (2007)
Scholars and practitioners alike share a widespread belief that the single greatest cause of wrongful conviction is erroneous eyewitness testimony. This conventional wisdom is almost certainly wrong. Conversational testimonydescribing earlier conversations or statements-is more common, more likely to be inaccurate, more likely to be believed by jurors, and more likely to produce irreversible errors than eyewitness testimony. Nonetheless, the dangers to the innocent posed by conversational testimony have been largely unrecognized. This Article highlights the case for further psychological and legal attention to conversational witnesses by comparing how the psychological processes and legal responses differ between eyewitness and conversational testimony. The Article concludes with implications for reform that may minimize the ongoing and unrecognized miscarriages of justice which result from erroneous conversational testimony